Inclusive experiences in supervised internship: Practices and learnings in the para athletics modality at the Amazonas Reference Centre (Research, Society and Development, 2025)
The research investigates inclusive experiences during supervised internship in the para-athletics modality, carried out at the Amazonas Reference Centre, focusing on teacher training and the promotion of integral health for people with disabilities. The study aims to analyse how the internship contributes to the development of sensitive, ethical, and humanised pedagogical practices that value the body, movement, and diversity as dimensions of the educational process. It adopts a qualitative and descriptive approach, characterised as an experience report, based on observation and reflective analysis of inclusive pedagogical practices developed within the context of para-athletics. The experiences were systematised through content analysis, identifying categories related to accessibility, autonomy, well-being, and meaningful learning. The results indicate that para-athletics represents a space of critical training, where educators learn to mediate inclusion processes and to recognise the emancipatory potential of human movement. It is concluded that the supervised internship enables the integration between theory and practice, promoting the understanding of adapted sport as an educational and citizenship tool, while strengthening the teaching commitment to equity and respect for diversity.